2006
DOI: 10.1161/01.res.0000252289.79841.d3
|View full text |Cite
|
Sign up to set email alerts
|

Wilms’ Tumor 1–Associating Protein Regulates the Proliferation of Vascular Smooth Muscle Cells

Abstract: Abstract-Smooth muscle cells (SMCs) are called on to proliferate during vascular restructuring but must return to a nonproliferative state if remodeling is to appropriately terminate. To identify mediators of the reacquisition of replicative quiescence, we undertook gene expression screening in a uniquely plastic human SMC line. As proliferating SMCs shifted to a contractile and nonproliferative state, expression of TIMP-3, Axl, and KIAA0098 decreased whereas expression of complement C1s, cathepsin B, cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
71
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 30 publications
4
71
1
Order By: Relevance
“…On the other hand, Small et al (19,20) reported that WTAP inhibits SMC proliferation and activates apoptosis by modulating the alternative splicing of the apoptosis regulator survivin. In addition, recent studies have shown that WTAP is overexpressed in glioblastoma (21) and cholangiocarcinoma (22) and promotes the migration and invasion of these cancer cells with an effect on cell proliferation under a condition of 1% FBS.…”
mentioning
confidence: 99%
“…On the other hand, Small et al (19,20) reported that WTAP inhibits SMC proliferation and activates apoptosis by modulating the alternative splicing of the apoptosis regulator survivin. In addition, recent studies have shown that WTAP is overexpressed in glioblastoma (21) and cholangiocarcinoma (22) and promotes the migration and invasion of these cancer cells with an effect on cell proliferation under a condition of 1% FBS.…”
mentioning
confidence: 99%
“…WTAP (Wilms tumor 1-associating protein) is a recently identified nuclear protein that, as its name implies, can interact with the WT1 suppressor protein (3,4). The precise molecular actions of WTAP are not well understood, but the importance of this protein is highlighted by the early lethality of WTAP-null mouse embryos (5,6).…”
mentioning
confidence: 99%
“…Furthermore, overexpression of WTAP in cultured SMCs suppressed their accumulation, whereas WTAP knockdown stimulated population growth. These effects were mediated, at least in part, by the capacity for WTAP to activate apoptosis (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…WTAP is a newly discovered component of the m6 A methyltransferase complex, which plays a critical role in epitranscriptomic regulation of RNA metabolism (Ping et al 2014). Recent studies show that WTAP inhibits the proliferation of vascular smooth muscle cells and endothelial cells and promotes apoptosis, regulating vascular remodeling (Small et al 2006(Small et al , 2007. During development of the vasculature IGF-1 was shown to downregulate WTAP, which is necessary for IGF-1 to confer its antiapoptotic effects, regulating smooth muscle cell fate (Small and Pickering 2009).…”
Section: Discussionmentioning
confidence: 99%